Intelectual propriety and technology transfer with blockchain - Alessandro Aveni (Revista Processus de Políticas Públicas e Desenvolvimento Social)
The article introduces the concept of using blockchain for intellectual property. It also presents an international example of the use of this technology for the World Intellectual Property Organization WIPO. The discussion on the use of advanced technologies is open in the technological and legal fields since in this border area there are many challenges and even more considering the global trends in the use of post-pandemic digital systems. The discussion shows that the transfer of technology and intellectual property is possible, and also wishes to promote a more agile international and local law system to receive requests from the market.